Bilateral orbital compartment syndrome in a patient with disseminated intravascular coagulation. (3rd September 2018) - Huang, Sonia; Sun, Michelle T.; Davis, Garry; Fitzgerald, Jude; Selva, Dinesh; Henderson, Tim
ABSTRACT: A 39-year-old male developed bilateral periorbital oedema and tense orbits in keeping with orbital compartment syndrome (OCS) shortly after presenting to the emergency department for uncontrollable epistaxis. Bilateral lateral canthotomy and inferior cantholysis was performed within 30 minutes of onset, with the left side further decompressed via superior cantholysis. Computed tomography demonstrated bilateral proptosis and optic nerve stretch, but no intraorbital haemorrhage or haematoma. Laboratory findings were consistent with disseminated intravascular coagulation (DIC) and sepsis of unknown origin. The right visual acuity recovered to 6/6 -2 from counting fingers, but the left eye failed to improve beyond light perception. This unique case of OCS is the first associated with DIC which had no evidence of intraorbital haemorrhage.